A efetividade dos sistemas de monitoramento e de avaliação das ações de assistência técnica e extensão rural implementadas pelo INCRA no Estado do Paraná - Campos, Ronilson Marques (2020)
The Technical Assistance and Rural Extension (ATER) policy provided to the beneficiaries of the National Agrarian Reform Program (PNRA) is one of the main actions implemented by the National Institute of Colonization and Agrarian Reform (INCRA) after the creation of the settlements, with the Superintendence of the INCRA in the State of Paraná invested, between 2003 and 2015, more than R$ 71 million in this action (INCRA, 2019). However, the monitoring and evaluation of the agreements and contracts signed for the provision of these services to settlers have not analyzed the effectiveness of this policy, that is, the changes that have occurred in the lives of the beneficiaries, from the moment they receive technical assistance. From this context, the main objective of this research was to analyze the monitoring and evaluation systems (M&E) adopted by INCRA/PR in the ATER agreements and contracts, between 2003 and 2015, to verify their effectiveness, according to the perception of the settled beneficiaries. Therefore, it starts with the theoretical debate on the effectiveness of social public policies (ARRETCHE, 1998; KRAFT; FURLONG, 2010; REZENDE ET AL, 2012; SANO E FILHO, 2013; SILVA AND BARROS, 2015) and the evaluation of systems monitoring and evaluation (BARBOSA, 2001; GUBERMAN; KNOPP, 2011) to carry out a case study of the Technical Assistance and Rural Extension (ATER) policy implemented by the Regional Superintendence of the National Institute of Colonization and Agrarian Reform (INCRA) in the State of Paraná. The main results show that INCRA/PR’s M&A systems have been guided by the evaluation of the efficiency and effectiveness of the actions, to the detriment of effectiveness, and that, in the perception of the beneficiaries, ATER is effective, mainly in the environmental and economic dimensions.